Prevalência, distribuição regional e fatores de risco da tuberculose bovina em Minas Gerais - Ana Paula Cunha Belchior (2000)
The aim of the present study was to estimate the regional prevalence and distribution of bovine tuberculosis in the State of Minas Gerais, Brazil, and to identify risk factors related to the disease. The area of the study is equivalent to 54% of the territory, 70% of all cattle and 75% of the herds of the State Comparative commercial skin test was performed in 22990 animals from 1586 herds distributed in seven strata. A questionnaire was applied in each farm to collect epidemiological and productivity data. In the area studied, 5% of the herds and 0,8% of the animals were positive to bovine tuberculosis. The higher prevalence of positive herds was found in "Alto Paranaíba" region, followed by the traditional milk-producting areas (South and Southwest regions) and the higher prevalence of positive animals was observed in the "Zona da Mata" region. Two criteria were compared for the interpretation of the skin test:the one recommended by OIE and the one currently used Brazil. The two interpretative criteria was differed greater in the number of positive herds tham in the number of positive animals. The risk factors to bovine tuberculosis found in this study - production system, genetic group, milking system, cooling of the milk and monitoring system - look like they are related to production intensification.